1983
DOI: 10.1093/clinchem/29.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygote detection in congenital adrenal hyperplasia.

Abstract: Detection of heterozygote carriers for congenital adrenal hyperplasia by use of a modified tetracosactide (a synthetic corticotropin) stimulation test with prior overnight dexamethasone suppression proved to have a diagnostic accuracy of 95%. Discrimination of heterozygotes from normals was best when we used a criterion based on the ratios of 17 alpha-hydroxyprogesterone to cortisol at baseline and at 30 min after intravenous administration of 250 micrograms of tetracosactide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The prevalence of classic 21-OH deficiency is high, affecting about 1 in 10,000 individuals (1, 4), whereas heterozygocity for this disorder varies considerably, ranging from 1 in 20 to 1 in 60 in large populations and ethnic groups (5,6). Following ACTH stimulation, carriers of 21-OH deficiency display increased secretion of cortisol precursors, including 17-hydroxyprogesterone (17-OHP), and lower concentrations of 11-deoxycorticosterone and aldosterone, compared with normal subjects (7)(8)(9)(10). In 50 -80% of 21-OH deficiency carriers, 17-OHP responses to ACTH stimulation fall above the 95th percentile for the control population (7)(8)(9)(10), indicating that the majority of these subjects may have mild impairment in cortisol biosynthesis and, consequently, compensatory increases of hypothalamic CRH secretion.…”
Section: -2236 2004)mentioning
confidence: 99%
“…The prevalence of classic 21-OH deficiency is high, affecting about 1 in 10,000 individuals (1, 4), whereas heterozygocity for this disorder varies considerably, ranging from 1 in 20 to 1 in 60 in large populations and ethnic groups (5,6). Following ACTH stimulation, carriers of 21-OH deficiency display increased secretion of cortisol precursors, including 17-hydroxyprogesterone (17-OHP), and lower concentrations of 11-deoxycorticosterone and aldosterone, compared with normal subjects (7)(8)(9)(10). In 50 -80% of 21-OH deficiency carriers, 17-OHP responses to ACTH stimulation fall above the 95th percentile for the control population (7)(8)(9)(10), indicating that the majority of these subjects may have mild impairment in cortisol biosynthesis and, consequently, compensatory increases of hypothalamic CRH secretion.…”
Section: -2236 2004)mentioning
confidence: 99%
“…Several studies from various groups have conveyed that between 50 and 80% of carriers exhibit a 17-OHP level after ACTH stimulation and that is above the 95th percentile of the control value [ 37 , 39 , 42 , 45 ]. The purpose of this study was to determine the frequency of identified defects of the CYP21A2 gene and also to weigh the regulatory 3′UTR region of the gene in a clinically symptomatic cohort of 169 females, characterized by hyperandrogenaemia.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to normal female individuals, female carriers of 21-OHD frequently demonstrate an exaggerated secretion of the 21-OH precursor 17-OHP after ACTH administration ( 51 ). It has been reported that 50-80% of carriers exhibit 17-OHP levels above the 95 th percentile of the control level after ACTH stimulation ( 51 , 52 , 53 ).…”
Section: Discussionmentioning
confidence: 99%